The Influence Of Internal Audit On The Effectiveness Of Internal Control Of Cash And Receivables (An Empirical Study At PT. Bank BJB Syariah KCP Sumedang) - Erpi Rahman (LPPM Universitas Sebelas April, 2023)
The Company has a goal of obtaining the maximum profit. Internal control is a process to achieve certain goals. The effectiveness of internal control has a major influence in directing the company to achieve its goals. Internal audit, which is one of the elements of internal control, has a comfortable influence on the trust of the entire company's internal control. The effectiveness of internal control can run well if the internal audit can run well. This study aims to determine the effect of internal audit on the effectiveness of controlling cash and receivables at PT. Bank BJB Syariah KCP Sumedang. By taking the sample using the saturated sample method, namely as many as 30 respondents. Data collection techniques using observation methods and distributing questionnaires to respondents. Technical data analysis using Statistical Package For Social Science (SPSS) 29. The analytical method used in this study is correlation coefficient analysis, analysis of the coefficient of determination, and hypothesis testing, namely the t test. The results of the t test regarding the effect of internal audit on the effectiveness of internal control of cash and receivables indicate a positive and significant influence as evidenced by the value of tcount = 4.636 > t table = 2.048. Based on the result of the determination test, internal audit has an effect of 43.3% while the remaining 56.7% is determined by other factors that are not included in the research variales. So it can be interpreted that Internal Audit has a fairly strong influence based on the criteria in table 3.4 on the effectiveness of Internal Control of Cash and Receivables at BJB Syariah Sumedang.